Efektivitas Berkumur Jus Wortel (Daucus Carota l.) Terhadap Indeks Plak Pasien Prolanis - Kusniati, Retno; Anwar, Saifuddin Ali; Fitri, Nurul (Jurnal Material Kedokteran Gigi, 2022)
The chronic disease management program (PROLANIS) seeks to tackle chronic diseases, such as Diabetes Mellitus and Hypertension. Data for 2018 Diabetes Mellitus in Kedungmundu Health Center were 3,165 cases and Hypertension as many as 4,417 cases. People with diabetes oral manifestations such as gingivitis, periodontitis, xerostomia and plaque accumulation. Hypertension sufferers with oral manifestations such as gingival hyperplasia and xerostomia. The purpose of this study to analyze the effectiveness of carrot juice (Daucus Carota L) gargling plaque the index prolanis patients Kedungmundu Public Health Center Semarang. This research is kind of quasi experimental which the research design is pretest-posttest with group design. The sampling technique in this study is purposive sampling. The treatment group using 100% carrot juice. Data analysis dependent t-test. The average of decreasing plaque index before gargling using carrot juice was 57,54 ± 27,07. The average of decreasing of in plaque index after gargling using carrot juice was 33,63 ± 23,36. Statistical test results showed that there were significant differences the Plaque Index of the treatment group p-value of 0,000 (p <0.05). Gargling using carrot juice is effective in order to decrease the plaque index of prolanis patients.